PELAKSANAAN INSPEKSI RAMP CHECK ANGKUTAN UMUM DI TERMINAL TIPE B WILAYAH UPT PPP MALANG BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Setiawan, Yeppy; Marwiyah, Siti; Widodo, Ernu (Gapenas Publisher, 2025)
The purpose of this study was to determine whether the Ramp Check inspections conducted by the Malang PPP Technical Implementation Unit (UPT) on public transport vehicles were in accordance with Road Traffic and Transportation Law No. 22 of 2009. As mandated by law, the main objective was to determine the extent to which these inspections ensured vehicle safety and roadworthiness. Problems with human resources, equipment, and inter-agency cooperation are some of the issues revealed by this study's examination. Government Regulation No. 79 of 2013 and Ministerial Regulation No. 132 of 2015 provide a clear legal basis; however, the analysis concludes that the implementation of inspections at Malang Type B Terminal is not ideal. This report further details the existing regulatory obstacles and offers suggestions on how to strengthen the inspection system. It concludes with recommendations on how to address issues with operational processes and law enforcement to improve regulatory compliance. The ultimate goal of this study is to help improve the Ramp Check system, which will result in safer roads and better public transport in Malang